Investigation of the Association between Facebook Connect Strategies and Academic Procrastination Behavior of Adolescents to Ongoing Different High Schools - Deniz, M. Engin; Uzun, A. Ensar (ICLEL CONFERENCES, 2016)
The aim of this research is examination the relationship between on going different High school adolescents connection the Facebook strategies with the academic procrastination behaviors. Academic Procrastination was examined whether differed by gender, frequency of use of Facebook, the type of high school and class level. Totaly 450 students, including 9th, 10th, 11th students, participate in this study. A stratified sampling method was selected. First, schools are subdivided into lower middle and upper socio-economic groups. Then students selected sample group was formed by random sampling method. This study is a descriptive study in the relational model. Relational screening model aims to determine the existence of the exchange agreement between two or more variables (Karasar, 2003). The research data was collected by Facebook connection strategies scale, Academic procrastination scale, Personal Information Form. Significant difference has been found in academic procrastination by frequency of using Facebook account of sample from the group of students' (F=5.48; p .05). Finally, it was observed that Facebook Connect strategies initiating (r:.337; p<.001), maintaining (r:. 223; p<.001), information-seeking (r:. 116; p<,05) at a scale of higher scores of students committed information search score rises.
Keywords: Puberty; Facebook Connect Strategies; Suspension; Acamedemic Procrastination Behavior; Education & Educational Research